RELATIONSHIP ALGEBRAIC EQUATIONS WITH (N,M)-FORMS, THEIR DEGREES AND RECURRENCE FRACTIONS - Заторський, Роман Андрійович; Ліщинський, Іван Іванович; Семенчук, Андрій Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
It analyzes the relationships (n,m)-forms type s_0 + s_1 [n]m +… + s_n − 1 [n]m^n−1, s_i , mQ with the generalized Diophantine equations Pell, algebraic equations n-th degree and recurrence fractions.